Детемір — унікальний аналог інсуліну продовженої дії - Малижев, В. О.; Сакало, О. А. (Clinical Endocrinology and Endocrine Surgery, 2008)
In the present review the analysis of published data about pharmacokinetic and pharmacodynamic peculiarities of insulin analogue detemir is presented in comparison with other insulin medications of long-term action-insulin NPH and glargin. This insulin analogue of basal type because of its structure have a particular mechanism of prolonged action due to detemir ability to combine with interstitial fluid and plasma albumin molecules. In spite of this in contrast of other analogues insulin detemir is water soluble with neutral pH and do not leave a sediment in tissues after injections. In treatment of diabetes mellitus type 1 and 2 patients detemir has a similar action on glycemia control as insulin NPH and glargin. However, with the detemir use the lesser variability of glucose levels is present during whole day. In the same time insulin detemir have a unique ability to penetrate in the liver and its action on this organ is more intensive than at the periphery. At last insulin detemir in contrast of other insulins can selectively penetrate in to the brain tissue restoring hypothalamus and brain cortex activity, increasing functioning of energetic metabolism control mechanism and mental work. These peculiarities of detemir envisage a new approach of insulin therapy which is not related only to glicemia control.